Opinion of young badminton players about the possibility of making changes to the regulations - Ortega-Toro, E.; Blanca-Torres, J. C.; Fernandez-Garcia, A. I.; Torres-Luque, G.; Gomez-Ruano, M. A. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: In order to ensure that the competition is a true formative medium, it is necessary that it be adapted to the needs, priorities and preferences of young athletes. In this sense, there are several authors who highlight the regulation as the key element to make the competition as a formative medium. There are few studies in which statutory changes are proposed in sport in general, indicating in all of them that an adequate regulatory modification allows an increase in their sport learning levels. However, most of the studies which are about on regulatory modifications propose the modifications after an only conceptual review. There are few studies that take into account the opinion of the coaches and experts on these possible modifications (Ortega. Castro, et al.. 2008). These opinions should be essential criteria to decide which modifications to make. To a much lesser extent, the opinion of the athletes is taken into account in order to carry out said regulatory modifications. Therefore, the main purpose of the present study is to know the opinion that young badminton players have about possible regulatory modifications on the current regulations used by the Spanish Badminton Federation. Methods: The determined sample was composed of 207 badminton under 14 players, who participated in the Spanish Championship by Autonomous Communities. Results: The most significant results indicate that the majority of players find the current regulation very adequate, although some of them would propose: a) a greater number of points in each set with respect to the usual ones b) the shuttlecock would be slower; c) the net should be lower. Conclusions: These values must be taken into account by the coaches and the sports federations, with the aim of being able to make regulatory adaptations which facilitate an adequate progress in the formation of the badminton player.